Implementation Strategics of Productive Waqf and Zakat Funding Integration Model Toward Sustainable Character Development: A Case Study of Universitas Airlangga - Wisudanto, Wisudanto; Thalib, Prawitra; Arif, Mochamad Shamsul; Kholiq, Mochamad Nur Kholiq Nur (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: This research aimed to implementation strategy on waqf and zakat funding to improve student character. This research took place at Universitas Airlangga students who want to participate in character development through the Griya Khadijah program.Design/Methodology/Approach: This research used a qualitative method with an exploratory analysis approach and case studies. Data were obtained from in-depth interviews, focus group discussions, and field observations. The collected data were analyzed using triangulation techniques and effectiveness analysis to create a funding integration strategy.Findings: The results of the research indicated that the integration of zakat and waqf funding can be implemented with 2 different entities (Nazhir and PUSPAS). Nazhir acts as a provider of initial investment and curriculum development costs until Griya Khadijah was ready to run. While the role of PUSPAS was to provide operational costs by financing scholarships for students participating in the Griya Khadijah program. This funding integration process had several consequences, such as in accounting and curriculum aspects.Research limitations/implications: Research contributed to the Sustainable Character development of temporary waqf studies in Indonesia. In addition, the proposed model can be the basis of reference for other nazhir in Indonesia.Originality/value: This paper proposes a model which similar, to implemented strategy the management of waqf and zakat to improve the character of Universitas Airlangga students at Griya Khadijah. The results of this study In the context of the curriculum, Griya Khadijah has a target output of students as Hafidz Quran memorizers and young entrepreneurs. Therefore, Griya Khadijah has 4 class schemes starting from basic, intermediate, and advanced so that the material delivered is on target.Â